ENDOMETRIAL PATHOLOGY BY ENDOMETRIAL CURETTAGE IN MENORRHAGIA IN PREMENOPAUSAL AGE GROUP - Riaz, Shazia; Ibrar, Faiza; Dawood, Nasira Sabiha; Jabeen, Alia (Journal of Ayub Medical College Abbottabad, 2010)
Background: Menorrhagia is objectively defined as blood loss greater than 80 ml or menstrual period lasting longer than 7 days. Dysfunctional uterine bleeding is responsible for 80% cases of Menorrhagia. Objective of this study was to find out the endometrial pathology and usefulness of hysterocopic directed endomentrial sampling in patient having menorrhagia in premenopausal age group. Methods: This prospective descriptive study was conducted at Unit 1 of the Department of Obstetrics and Gynaecology, Fauji Foundation Hospital Rawalpindi, Pakistan from January to December 2007. During the study period, 100 patients with menorrhagia in age group 35-50 years were selected after fulfilling the inclusion criteria. These patients were selected from Gynaecology out patient department. After detailed history, examination and ultra sonography, they were admitted and hysteroscopic directed endometrial sampling was done endometrial samples were sent for histopathology to find out the endometrial pathology. Results: The selected patients of my study with menorrhagia were scattered over all premenopusal age groups >35 years. It was observed that 67 patient were above the age of 40 years. The analysis of histopathology reports of endometrial curettage revealed proliferative endomentrium in 33%, cystic hyperplasia’s in 25% and carcinoma endometrium in one case. Cystichyperplasia and proliferative endometrium were found in menorrhagic women over 40 years of age. Adenoicarcinoma was found in a single premenopausal women of 48 years. Conclusion: All patients having menorrhagia above 40 years should be screened for any endometrial pathology. Accurate analysis of endometrial sampling is the key to effective therapy and optimal out come. Keyword: Hysterocopic guided endometrial curettage, Menorrhagia, Premenopause DUB